Hematopoietic stem cell transplantation in the treatment of multiple myeloma - Maiolino,Angelo (2002)
Multiple myeloma is a malignant clonal plasma cell disorder that accounts for about 10% of all hematological malignancies. Conventional melphalan-based chemotherapy produces less than 5% of complete remission rates, with less than 5% of patients surviving 10 years or more. The VAD regimen is very effective to induce cytoreduction, but does not prolong event free survival or overall survival. High-dose therapy with autologous bone marrow or peripheral blood stem cell support induces complete remission in 30%-50% of patients, with a very low transplant related mortality (<5%). Both event free survival and overall survival are prolonged with High-dose therapy, but relapses continue to be a major problem. A subset of patients (chromosome 13 abnormalities and high level of beta2-microglobulin at diagnosis) at high risk of relapse has been identified. Double transplants and post-transplant strategies, with the use of alpha interferon, thalidomide, or combined chemotherapy, are additional measures used to reduce the incidence of relapse. Allogeneic transplants can induce durable molecular remissions. However, the very high (30%-50%) transplant-related mortality limits the application of this procedure. The emerging concept of non-myeloablative transplants may be a very attractive alternative to improve these results. This strategy may be associated with lower transplant related mortality, and yet provide a graft versus myeloma effect, potentially increasing event free survival and overall survival.